Analysis of the functional gene structure and metabolic potential of microbial community in high arsenic groundwater. (15th October 2017) - Li, Ping; Jiang, Zhou; Wang, Yanhong; Deng, Ye; Van Nostrand, Joy D.; Yuan, Tong; Liu, Han; Wei, Dazhun; Zhou, Jizhong
Abstract: Microbial functional potential in high arsenic (As) groundwater ecosystems remains largely unknown. In this study, the microbial community functional composition of nineteen groundwater samples was investigated using a functional gene array (GeoChip 5.0). Samples were divided into low and high As groups based on the clustering analysis of geochemical parameters and microbial functional structures. The results showed that As related genes ( arsC, arrA ), sulfate related genes ( dsrA and dsrB ), nitrogen cycling related genes ( ureC, amoA, and hzo ) and methanogen genes ( mcrA, hdrB ) in groundwater samples were correlated with As, SO4 2−, NH4 + or CH4 concentrations, respectively. Canonical correspondence analysis (CCA) results indicated that some geochemical parameters including As, total organic content, SO4 2−, NH4 +, oxidation-reduction potential (ORP) and pH were important factors shaping the functional microbial community structures. Alkaline and reducing conditions with relatively low SO4 2−, ORP, and high NH4 +, as well as SO4 2− and Fe reduction and ammonification involved in microbially-mediated geochemical processes could be associated with As enrichment in groundwater. This study provides an overall picture of functional microbial communities in high As groundwater aquifers, and also provides insights into the critical role of microorganisms in As biogeochemical cycling. Graphical abstract: Image 1 Highlights: Samples were divided into low and high arsenic (As) groups based on geochemical parameters and microbial functional structures. Genes arsC, arrA, dsrA / B, ureC, amoA, hzo, mcrA, hdrB were correlated with As, SO4 2−, NH4 + or CH4, respectively. As, TOC, SO4 2−, NH4 +, ORP and pH were important factors shaping the functional microbial community structure. Alkaline and reducing conditions could be associated with As enrichment in groundwater. An overall picture of functional microbial communities in high As aquifers is provided.